Faktor kecemasan yang mempengaruhi kemampuan membaca nyaring pada mahasiswa: Faktor kecemasan yang mempengaruhi kemampuan membaca nyaring pada mahasiswa - Sujariati, Sujariati; Mallapiang, Yassir; Nurhayati, Nurhayati (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
The purpose of this study will to determine the anxiety factor of students in reading English aloud in class. The methodology used in this research is descriptive qualitative. The research data were obtained using two instruments, namely observation and a questionnaire containing questions related to what are the causal factors in reading anxiety. The research method used is descriptive qualitative. The population in this study were students from Universitas Muhammadiyah Makassar. The number of samples used was 13 students in 1 class. The results finding provide by qualitatively and quantitatively. The result of the study show that the level of anxiety to read aloud with an average of 61.03%, with the calculations obtained from the questionnaire data. From the observation results show that there are two factors in anxiety when reading aloud, namely internal and external factors. Among these factors, internal factors show a higher or prominent level of anxiety on aspects of worrying about reading effects and fear of making mistakes. Which can be minimized with several stages, preparation, relaxation and positive thinking.